2006
DOI: 10.1074/jbc.m512826200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Estradiol/Estrogen Receptor α-dependent Transcriptional Mechanism Controls Expression of the Human Prolactin Receptor

Abstract: 2 -activated transcriptional expression of the hPRLR through PIII. Estradiol produced in breast stroma and adipose tissue, which are major sources of estrogen in post-menopausal women, could up-regulate hPRLR gene expression and stimulate breast tumor growth. Prolactin (PRL),2 a hormone of the lactogen/cytokine family, is produced in the anterior pituitary gland and exerts diverse cellular actions through its transmembrane receptors (PRLR) in several target tissues. Prolactin is a major factor in the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 51 publications
5
76
2
3
Order By: Relevance
“…A study of the rat PrlR promoter region III showed that it has a C/EBPβ and a nearly adjacent Sp1 site in its proximal region . The proximal human promoter retains these response elements and is, in fact, 81 % similar in sequence to the rat promoter (Dong et al, 2006), as is the mouse PIII promoter (Ormandy et al, 1998). The rat generic PrlR PIII promoter is constitutively activated by C/EBP and Sp1 in liver and gonadal cells (Hu et al, 1996;Moldrup et al, 1996); the human PrlR promoter in MCF7 breast cancer cells is activated by E acting through its receptor which tethers to these same transcription factors (Dong et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A study of the rat PrlR promoter region III showed that it has a C/EBPβ and a nearly adjacent Sp1 site in its proximal region . The proximal human promoter retains these response elements and is, in fact, 81 % similar in sequence to the rat promoter (Dong et al, 2006), as is the mouse PIII promoter (Ormandy et al, 1998). The rat generic PrlR PIII promoter is constitutively activated by C/EBP and Sp1 in liver and gonadal cells (Hu et al, 1996;Moldrup et al, 1996); the human PrlR promoter in MCF7 breast cancer cells is activated by E acting through its receptor which tethers to these same transcription factors (Dong et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The mouse PrlR promoter III (824-PIII; GeneBank accession #AC074172; a kind gift from Dr. Robert Callahan, NCI) including the 5' flanking region/exon 1 (Dong et al, 2006) and contained within a pGL3 basic vector (Promega, Madison, WI) was PCR cloned with 5 Prime (Gaithersburg, MD) using XhoI/HindIII primers to make the −439/−179-PIII (-439-PIII) construct. Primers (Table 1A) were used at a concentration of 6 μM each with 50 ng of 824-PIII.…”
Section: Mouse Prlr Promoter Constructsmentioning
confidence: 99%
See 3 more Smart Citations